The Impact of Digital Leadership on Corporate Social Responsibility: A Study in Bursa - Kustepe, Veli; Ruzgar, Nilufer (European Scientific Journal, ESJ, 2026)
In today’s business environment, digitalization has become a key driver of sustainable competitive advantage. Within this context, digital leadership plays a critical role in shaping organizational strategies and enhancing corporate social responsibility (CSR) practices. This study aims to examine the impact of digital leadership on CSR perceptions within an organizational setting. The research was conducted in Bursa, Turkiye, using a survey method. Data were collected from 332 participants through a structured questionnaire, including the Corporate Social Responsibility Scale (Türker, 2006) and the Digital Leadership Scale developed by Büyükbeşe et al. (2022). The collected data were analyzed using SPSS 26.0, employing descriptive statistics and simple linear regression analysis. The findings reveal a positive and statistically significant relationship between digital leadership and CSR perception (p < 0.05). The results indicate that higher levels of digital leadership are associated with stronger CSR awareness among employees. This study contributes to the literature by providing empirical evidence from a developing country context and offers practical implications for integrating digital leadership into CSR strategies.